Peningkatan Komunikasi Antarbudaya dalam Program Saweu Sikula di Sekolah Sukma Bangsa Bersama Mahasiswa Eropa - Azhari, Teuku; Sahputri, Juwita; Mukhlis, Mukhlis (Universitas Malikussaleh, 2025)
Intercultural Communication in the Context of Education in the Era of Globalization is very important. The communication built must be effective and bridge communication across cultures and races. Language plays an important role in cross-cultural communication. The good use of language can prevent us from misunderstandings and conflicts caused by language interpretation (Putranto et al., 2024). The low intercultural understanding among local students is one of the main problems faced in the school environment. Many students have not had the opportunity to interact and exchange ideas with people outside their culture and language. Globalization has allowed inter-country and intercultural interactions to become more intense, including in the fields of Education, Schools and universities. The saweu sikula activity together with foreign students was carried out at the Sukma Bangsa school in Lhokseumawe City. This activity begins with making an appointment and a plan for the event (run-down) of the activity. The activity was held on Tuesday, October 1, 2024, precisely at Sukma Bangsa High School, Lhokseumawe City. The activity was attended by the Board of Teachers, committee students, Unimal lecturers, and 10 European, French, Dutch, and Norwegian students. This activity brings a lot of benefits to both parties, students and students. First, increased self-confidence. Exposure to foreign cultures and direct interaction can increase self-esteem. Both students and foreign students can share each other's culture and enrich each other's cultural scientific treasures. Third, all participants can strengthen their ability to interact with new people so that they are not awkward in communication at the beginning of the day. It is hoped that this activity can continue so that it can develop communication skills.